Sovereign defaults before domestic courts - Kupelyants, Hayk ([Oxford] : Oxford University Press, 2018)
This work examines sovereign debt litigation before the English and New York courts. The text sets out parties' litigation choices at various stages of proceedings and provides the legal background against which parties to a sovereign bond may wish to negotiate. It provides timely clarity and critical analysis of a growing area of law.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 19, 2018).
Keywords: Debts, Public; Debts, Public -- Law and legislation